CSR in China Research: Salience, Focus and Nature - Moon, Jeremy (Journal of business ethics, 2010)
This article investigates the development of research in the field of CSR in China. The justification for this is that (i) there is evidence that CSR is emerging as a management practice and management field internationally; (ii) there is a general interest in the distinctiveness or comparability of management and management research in Asia and China; (iii) there is evidence that CSR is growing as a management issue in China; and (iv) yet, the mainsprings of this are very different from those in Western business systems. This article adopts a methodology used in wider analysis of CSR in management research (Lockett et al., Journal of Management Studies 43, 2006, 115) to bring forth comparisons over the salience, focus and nature of CSR in China research. It finds a rapidly growing salience of CSR in China research, albeit from a low base. It parallels Lockett et al.’s (2006) finding of a ‘thickening’ of CSR research focus from early concerns with Ethical issues only to greater attention to Social, Environmental and Stakeholder concerns. It also generally parallels Lockett et al.’s (2006) findings on the balance of research methodologies deployed. The significance of the findings for future CSR research in China is considered both for the notion of a CSR field of research and for our understanding of the development of CSR in China.